Process validation, current good manufacturing practice production, dosimetry, and toxicity studies of the carbonic anhydrase IX imaging agent [111In]In‐XYIMSR‐01 for phase I regulatory approval. (4th March 2021) - De Silva, Ravindra A.; Gorin, Michael A.; Mease, Ronnie C.; Minn, Il; Lisok, Ala; Plyku, Donika; Nimmagadda, Sridhar; Allaf, Mohamad E.; Yang, Xing; Sgouros, George; Rowe, Steven P.; Pomper, Martin G.
Abstract : [ 111 In]In‐XYIMSR‐01 is a promising single‐photon emission computed tomography (SPECT) imaging agent for identification of tumors that overexpress carbonic anhydrase IX. To translate [ 111 In]In‐XYIMSR‐01 to phase I trials, we performed animal toxicity and dosimetry studies, determined the maximum dose for human use, and completed the chemistry, manufacturing, and controls component of a standard regulatory application. The production process, quality control testing, stability studies, and specifications for sterile drug product release were based on United States Pharmacopeia chapters <823> and <825>, FDA 21 CFR Part 212. Toxicity was evaluated by using nonradioactive [ 113/115 In]In‐XYIMSR‐01 according to 21 CFR Part 58 guidelines. Organ Level INternal Dose Assessment/EXponential Modeling (OLINDA/EXM) was used to calculate the maximum single dose for human studies. Three process validation runs at starting radioactivities of 800 MBq were completed with a minimum concentration of 407 MBq/ml and radiochemical purity of ≥99% at the end of synthesis. A single intravenous dose of 55 μg/ml of [ 113/115 In]In‐XYIMSR‐01 was well tolerated in male and female Sprague–Dawley rats. The calculated maximum single dose for human injection from dosimetry studies was 390.35 MBq of [ 111 In]In‐XYIMSR‐01. We have completed toxicity and dosimetry studies as well as validated a manufacturing process to test [ 111 In]In‐XYIMSR‐01 in a phase I clinical trial. Abstract : We have completed toxicity and dosimetry studies as well as validated a manufacturing process for clinical translation of [ 111 In]XYIMSR‐01 targeting carbonic anhydrase IX. Radiolabeling yield and radiochemical purity averaged 51% and ≥99%, respectively. Specific radioactivity averaged 223 GBq/μmol. [ 111 In]In‐XYIMSR‐01 is poised for a phase I trial.